Misdecoding of rare CGA codon by translation termination factors, eRF1/eRF3, suggests novel class of ribosome rescue pathway in S. cerevisiae. (11th December 2018) - Wada, Miki; Ito, Koichi
Abstract : The CGA arginine codon is a rare codon in Saccharomyces cerevisiae . Thus, full‐length mature protein synthesis from reporter genes with internal CGA codon repeats are markedly reduced, and the reporters, instead, produce short‐sized polypeptides via an unknown mechanism. Considering the product size and similar properties between CGA sense and UGA stop codons, we hypothesized that eukaryote polypeptide‐chain release factor complex eRF1/eRF3 catalyses polypeptide release at CGA repeats. Herein, we performed a series of analyses and report that the CGA codon can be, to a certain extent, decoded as a stop codon in yeast. This also raises an intriguing possibility that translation termination factors eRF1/eRF3 rescue ribosomes stalled at CGA codons, releasing premature polypeptides, and competing with canonical tRNA ICG to the CGA codon. Our results suggest an alternative ribosomal rescue pathway in eukaryotes. The present results suggest that misdecoding of low efficient codons may play a novel role in global translation regulation in S. cerevisiae . Abstract : One of the rare codons in Saccharomyces cerevisiae, CGA, was found to be misdecoded as stop‐codon to a certain extent by the eRF1/eRF3 translation termination complex. Our genetic study of eRF1, a protein tRNA mimic canonically recognizing all three stop codons, suggests a novel class of ribosome rescue pathway for the inefficient translation.